Double-chambered left ventricle - Islam F.H. Ali; Khalid Y Tohamy; Mousa Akbar (SpringerOpen, 2012)
We describe a rare congenital anomaly in a 39-year-old woman who was referred for a preoperative echocardiographic assessment in February 2012. A double-chambered left ventricle was suspected on transthoracic echocardiography and was confirmed by transesophageal echocardiography.